Influence of light intensity and temperature on antioxidant activity in Premna serratifolia L - Chua, I.Y.P; King, P.J.H; Ong, K.H; Sarbini, Shahrul Razid; Yiu, P.H (Sociedad Chilena de la Ciencia del Suelo, 2015)
Premna serratifolia has been used to treat inflammatory disorders because it was believed to have antioxidant properties. However, scientific research on this species is currently lacking. This work assesses the antioxidant activity of P. serratifolia in relation to light intensity and temperature. Harvesting time significantly influenced the antioxidant activities in P. serratifolia leaves; the highest 1,1-diphenyl-2-picryl-hydrazil (DPPH) free radical scavenging activity and lowest flavonoid and phenolic contents were observed at 9 am. The opposite trend was observed at 12 noon. Temperature had a significant influence on the DPPH free radical scavenging activity and phenolic content. The DPPH antioxidant activity was negatively correlated with light intensity. The results of this study indicated that harvesting time of P. serratifolialeaves should be tailored according to the preferred antioxidant activity.